Contributions to the taxonomy, identification, and biogeography of the Palaearctic species of Cymodusa Holmgren (Hymenoptera: Ichneumonidae: Campopleginae) - Vas, Zoltán (Zootaxa, 2022)
In this paper Cymodusa irata sp. nov. is described from Turkmenistan, and two new synonyms are proposed: Cymodusa longiterebra Dbar, 1985 is considered a junior subjective synonym of Cymodusa nigra Šedivý, 1965, and Cymodusa ancilla (Seyrig, 1927) is considered a junior subjective synonym of Cymodusa australis (Smits van Burgst, 1913). New Palaearctic distributional records are given: Cymodusa australis (Smits van Burgst, 1913) is first reported from Bulgaria, Croatia, Hungary, Kosovo, North Macedonia and Serbia; Cymodusa declinator (Gravenhorst, 1829) from Hungary and Romania; Cymodusa exilis Holmgren, 1860 from Hungary; Cymodusa leucocera Holmgren, 1859 from Mongolia and Slovakia; Cymodusa nigra Šedivý, 1965 from Bulgaria, Greece, Kosovo and North Macedonia; and Cymodusa tibialis Dbar, 1985 from North Macedonia. Additionally, some formerly published distributional records are corrected.